2009
DOI: 10.1111/j.1439-0531.2007.01030.x
|View full text |Cite
|
Sign up to set email alerts
|

Transduction and Transplantation of Spermatogonia into the Testis of Ram Lambs through the Extra‐testicular Rete

Abstract: Spermatogonial transplantation will provide a new way to study spermatogenesis in domestic animals, disseminate male genetics and produce transgenic animals, if efficiency can be improved. We evaluated a 'surgical' method for transplanting donor cells into testes of ram lambs, where the head of the epididymis is reflected, and a catheter introduced into the extra-testicular rete testis. We also tested transduction of ram spermatogonia with a lentiviral (LV) vector as a means to identify permanent colonization,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…The greater availability of stem cell niches in irradiated testes would allow more stem cell colonization. Using the irradiation scheme proposed herein combined with the enrichment of donor cells, the efficiency of the technique could likely be improved [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The greater availability of stem cell niches in irradiated testes would allow more stem cell colonization. Using the irradiation scheme proposed herein combined with the enrichment of donor cells, the efficiency of the technique could likely be improved [25].…”
Section: Discussionmentioning
confidence: 99%
“…There are two ways to heighten the efficiency of germ cell transplantation, namely, suitable preparation of the recipient's testis [23] or increased purity of undifferentiated spermatogonia in the donor cell isolation [24,25]. Although donor cells can colonize unprepared recipient testes [10,23], colonization efficiency can be enhanced significantly by providing more stem cell niches in recipient testis for transplanted germ cells [19,24].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies showed that male adult GCs or spermatogonial stem cells located at the germinal epithelium and formed colonies after transplantation into the testis (39, 40). In the current study, we observed only one possible colony of transplanted cells formed in the testis of the 4-week group (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Germ cell transplantation in the rodent model has proven to be an invaluable tool for the study of spermatogenesis and spermatogonial stem cell biology (Brinster & Avarbock 1994, Brinster & Zimmermann 1994, Brinster 2007. The technique has now also been successfully established in pigs (Honaramooz et al 2002a), goats (Honaramooz et al 2003a, 2003b, 2008b, cattle (Izadyar et al 2003, Herrid et al 2006, monkeys (Schlatt et al 1999(Schlatt et al , 2002a sheep (Rodriguez-Sosa et al 2006, 2009), and dogs (Kim et al 2008; and although its use in these species is now a realistic option, further studies are needed before this approach becomes more widely applicable (Dobrinski & Travis 2007). One current limitation is that germ cell transplantation to study spermatogenesis in these species and to manipulate their germ cells is logistically difficult and expensive.…”
Section: Introductionmentioning
confidence: 91%